An Algorithm for Reselecting a Reference Objects - Bondarenko, N. N. (Pattern recognition and image analysis, 2018)
The problem of optimally choosing a learning object is studied. The definition of essential totality of precedents is given. It is shown that an iterative procedure for generating the essential totality of precedents exists. The algorithm operation is checked on model data.